Effect of Non-Slip Socks-Induced Foot Stability on Agility in Healthy Elderly Women - Tae-Seok Jeong; Chang-Hwa Joo (Asian Society of Kinesiology, 2022)
OBJECTIVES The risk of falls increases due to decrease in balance ability in elderly. A safe environment that can prevent slipping in daily life is required to prevent falls. The purpose of this study is to analyze the effect of socks with non-slip pads on improving foot stability and balance in the elderly. METHODS Sixteen older women aged 67-87years complete tests while wearing non-slip socks and/or normal socks. Measurements were taken for body composition, static and agility/dynamic balance, and self-reported wearing sensation. RESULTS Agility/dynamic balance was higher in the non-slip socks group than that in the normal socks group (p <0.05). The static balances did not differ significantly between the two groups (p>0.05). There were no differences between the two groups in terms of comfort, thermal, wet, tactile, and fit sensations according to the wearing of the socks (p>0.05). Significant higher stability sensation was observed in non-slip socks group than normal socks group (p <0.05). CONCLUSIONS These results suggested that the use of non-slip socks will help to prevent falls that may occur during indoor or outdoor activities and also improve exercise performance in the elderly.